Diversity of energy-saving control strategy for a parallel chilled water pump based on variable differential pressure control in an air-conditioning system. (August 2015) - Xuefeng, Liu; Jinping, Liu; Zhitao, Lu; Kongzu, Xing; Yuebang, Mai
Abstract: An analytical model of a parallel chilled water pump set was established in this study. The bypass-loop adjustment characteristic was found to be a key component of this model. A pump set consisting of four of the same type of pumps was the focus of this study, and the running characteristics for five types of control strategies were examined in detail: the control strategy of the power frequency pump quantity control, the hybrid control strategy of a single pump of variable frequency combined with power frequency pump quantity control, the control strategy of two pumps of synchronous variable frequencies, the control strategy of three pumps with synchronous variable frequencies, and the control strategy of four pumps with synchronous variable frequencies. These strategies were analyzed under different supply–return water differential pressures. It was proposed that the hybrid control strategy of single pump variable frequency combined with power frequency pump quantity control is most suitable for variable flow to the chilled water system under a low flow ratio or a high supply-return water differential pressure. Highlights: Operation characteristics model of parallel pump set is built based on bypass loop. Operation characteristics are analyzed in multiple differential pressure conditions. Control strategy has remarkable selectivity to flow and differential pressure. Single pump frequency is a more suitable in high differential pressure condition.